Cannabinoidergic Regulation of the Functional State of the Heart. The Role of the Autonomic Nervous System; Neuroscience and Behavioral Physiology; Vol. 49, No. 3 - Krylatov A. V. Andrey Vladimirovich; Maslov L. N. Leonid Nikolaevich; Nam I. F. Irina Feliksovna; Bushov Yu. V. Yuriy Valentinovich (2019, 2019)
Title screen